2015
DOI: 10.1007/s00213-015-3937-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the long-lasting consequences of adolescent ethanol exposure for the rewarding effects of cocaine in mice

Abstract: The effects of intermittent exposure to ethanol during adolescence are evident in adulthood, during which greater sensitivity and intake of cocaine is observed and differ in each sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 60 publications
3
22
1
1
Order By: Relevance
“…The BED participants and the obese controls were well-matched with respect to BMI, and in both groups their mean scores were in the Class II obesity range (viz., [35][36][37][38][39][40]. Unexpectedly, however, BED status did not moderate either the emotional responses or the appetite/food consumption responses to a dose of MP.…”
Section: Binge-eating and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…The BED participants and the obese controls were well-matched with respect to BMI, and in both groups their mean scores were in the Class II obesity range (viz., [35][36][37][38][39][40]. Unexpectedly, however, BED status did not moderate either the emotional responses or the appetite/food consumption responses to a dose of MP.…”
Section: Binge-eating and Obesitymentioning
confidence: 99%
“…Nevertheless, our results are in agreement with preclinical studies carried out over longer-term exposure to addictive substances. 37,38 Secondly, we did not take account of the menstrual cycle of the women in our study, or whether they were taking oral contraceptives. Given the established role of estrogen in moderating responsiveness to stimulant medications, 39 it will behoove future researchers to control for hormonal fluctuations in drug-challenge protocols.…”
Section: Limitationsmentioning
confidence: 99%
“…Several previous studies examined whether prior alcohol exposure increases cocaine conditioned place preference (CPP). In four studies, adolescent mice (Mateos-Garcia et al, 2015;Molet et al, 2013) or rats (Hutchison and Riley, 2012), or adult rats (Hutchison and Riley, 2012) that were pre-exposed to alcohol showed increased cocaine CPP. In contrast, Le Pen et al (1998) reported that alcohol preexposure in adult rats decreased subsequent cocaine CPP in low but not high alcohol drinkers.…”
Section: Introductionmentioning
confidence: 99%
“…Además, los resultados de este estudio han mostrado diferencias de sexo en el CPL inducido por cocaína. Ratones machos mostraron una preferencia condicionada inducida por la cocaína (20 mg/kg) más alta que las hembras, dado que pasaron significativamente más tiempo en el compartimento emparejado con droga en la prueba Post-C. Esta diferencia de sexo en el paradigma CPL, que no había sido observado en estudios anteriores (Bobzean, Dennis, Addison y Perrotti, 2010;Hilderbrand y Lasek, 2014;Mateos-García et al, 2015), puede deberse al número elevado de sujetos usados por grupo (n > 30). No obstante, esta preferencia más alta en los machos también se observó en el número más elevado de reinstauración en la preferencia condicionada con dosis de cocaína menores.…”
Section: Discussionunclassified